Analisis Minat Belajar Siswa Pada Proses Pembelajaran Daring Di Kelas Va SDN Lembursitu - Dewi Santika; Astri Sutisnawati; Din Azwar Uswatun (STKIP Andi Matappa Pangkep, 2020)
This study aims to analyze the student learning interest the process of online learning in SDN Lembursitu Kota Sukabumi, and the role of parents in the online learning process. This study qualitative descriptive research methods with research subjects are teacher, parents and students. The technique for data collection using interviews, questionnaires and documentation. Technique semi-structed interview and open questionnaire. Data analysis techniques with three stage are data reduction, data display and data conclusion/verification. Covid-19 pandemic in Indonesia has an impact on students interest in learning, when the learning process switches to online learning it results in decreased student interest marked by the lack of active student participation whe following the learning process. In this case parents are very involved in the implementation of the learning process online, parents play a role in guilding students when doing assignments, providing facilities in the form of phone and internet quota, motivate students to study spirit, help and supervise students when carrying out the learning process so that students follow the learning process well and smoothly by always coordinating with the teacher regarding the development of student learning.